Are Noradrenergic Transmission Reducing Drugs Antidepressants? - Fitzgerald, Paul J. (Frontiers in Behavioral Neuroscience, 2021)
Major depressive disorder (MDD) remains a significant public health problem worldwide, and revised treatment strategies are therefore urgently needed, including the creation of novel antidepressant compounds or using existing molecular entities in new ways. Etiologic theories of MDD from decades ago have suggested that synaptic deficiencies of monoaminergic neurotransmitters play a causative role in this neuropsychiatric disorder, and that boosting monoamines with drugs such as SSRIs, SNRIs, TCAs, and MAOIs has antidepressant effects and in some individuals can even induce hypomania or mania. While other factors, such as various intracellular molecular pathways and hippocampal neurogenesis, undoubtedly also play a role in MDD, monoaminergic boosting drugs nonetheless have clearly demonstrated antidepressant properties. There is also, however, a body of studies in the preclinical literature suggesting that monoaminergic transmission reducing drugs, including noradrenergic ones, also have antidepressant-like behavioral properties in rodents. Given that there is increasing evidence that the monoamines have u-shaped or Janus-faced dose-response properties, in which a mid-range value is “optimal” in a variety of behavioral and physiological processes, it is plausible that either too much or too little synaptic norepinephrine in key circuits may exacerbate MDD in some individuals. Here we briefly review rodent depression-related behavioral data, focusing on the forced swim test, from three major classes of noradrenergic transmission reducing drugs (alpha2 agonists, beta blockers, alpha1 antagonists), and find much support for the hypothesis that they have antidepressant-like properties. Whether these drugs are antidepressants in human subjects remains to be determined.